Numerical investigation of the role of masonry typology on shear strength. (1st August 2019) - Zhang, Shenghan; Beyer, Katrin
Highlights: The influence of masonry typologies on shear strength is studied through numerical simulations. Mann and Müller's theory overestimates the effect of interlocking. The size effect on the shear strength is moderate for masonry walls. Compared to LMT, block area ratio is a better indicator of masonry shear strength. LMT and block area ratio correlate well with masonry strength for shear failure. Abstract: The force-displacement behavior of masonry elements depends on the properties of their constituents, mortar and unit, as well as on their typology, i.e., the shape and size of the units and the patterns they generate. Up until now, only few numerical studies investigated the influence of the masonry typology on the mechanical properties of the masonry. The lack of research is caused by both the difficulty of generating specific stone masonry typologies, which vary depending on geographical regions, construction periods, and building technology, and the difficulty of conducting detailed micro-modeling analyses. Building on our recent developments of a typology generator and a detailed micro-modeling method based on cohesive elements, we investigate the relation between masonry typology and maximum shear resistance. After calibration of the model for shear-compression tests, the study examines the validity of Mann and Müller's theory at the nonlinear stage, clarifies the role of the line of minimum trace in characterizing effective interlocking, and investigates the correlation of maximum shear resistance with various indexes. We show that the effect of the interlocking between units on the shear strength is overestimated by the Mann-Müller model. This study provides a fundamental contribution to our understanding of the influence of masonry typology on the masonry shear strength.